Cystic Ovarian Disease in Rathi Cattle - Gupta, G N; Joshi, B K; bishnoi, B L; Gupta, A K; Joshi, R K; Vyas, S K; Gupta, K A; Pareek, P K; Sharma, S S (Annals of Arid Zone, 2016)
Cystic ovarian disease (COD) was studied in Rathi cows. The overallincidence of COD in rural and urban areas was 2.12 and 0.87%, respectively.Cysts were usually singie, smaller in size and located mostly on the right ovary(56.03%) with nymphomania as the predominant clinical sign. Biochemical estimationsin serum revealed significantly higher values of chloride and significantly lowervalues of inorganic phosphorus (P